A computational spectral imager for aurora observation based on cascaded overcomplete dictionary - Yuanhao Zheng; Zejun Hu; Jian Pei; Yao Chen; Lin Yang (Advances in Space Research, 2026)

Oil phase-driven nanoemulsions improve CoQ10 stability, in vitro bioaccessibility and ex vivo intestinal uptake - Xia Jin; Peng Wu; Ni Wang; Ping Zhang; Cheng Li; Zejun Hu; Wenhao Zhao; Xiao Dong Chen (Food Research International, 2026)

Fine-mapping and candidate gene analysis of qFF3.1 conferring fruit firmness in a modern tomato variety - Yunhao Han; Xin Li; Can Zhu; Yonglian Wang; Junling Hu; Shumin He; Saifeng Guo; Xiaoxiao Lu; Chunyang Pan; Zejun Huang; Yanmei Guo; Xiaoxuan Wang; et al. (Theoretical and Applied Genetics, 2026)

The role of thermal energy in the electrical process of electrically controlled solid propellants - Zejun Hu; Jianjun WU; Zhicheng He; Yu Zhang; Qinhui Peng; Shiqichang Wu; Yuji Chen (Fuel, 2026)

Neuropeptide FF enhances antimicrobial defense by promoting intestinal barrier function in grass carp (Ctenopharyngodon idella) - Pingyuan Li; Jiaxin Liu; Jiayi Hu; Ye Yang; Yujun Liu; Chuyi Zeng; Yiyang Tang; Jianguang Cai; Zejun Zhou (Fish & Shellfish Immunology, 2026)

Expanding protected areas to conserve habitat connectivity for giant panda - Hu Zhang; Zongkun Shi; Thomas Connor; Yujun Wang; Desheng Li; Dunwu Qi; Hongbo Yang; Xiaodong Gu; Weihua Xu; Zhenhua Zang; Jindong Zhang; Zejun Zhang (Biological Conservation, 2026)

pH-sensitive, edible chitosan-based hydrogels with extremely high swelling and reinforced mechanics: A chemical-free crosslinking strategy for gastric retention - Ke Wang; Peng Wu; Zejun Hu; Xiao Dong Chen (Food Hydrocolloids, 2025)

Grass carp HB-EGFa enhances resistance to Aeromonas hydrophila infection by fortifying gut mucosal barrier function - Pingyuan Li; Chuyi Zeng; Yujun Liu; Jiayi Hu; Ye Yang; Yiyang Tang; Zejun Zhou; Qinbo Qin (Fish & Shellfish Immunology, 2025)

Corrigendum to “Regulation of cell migration through cross-sectional morphology design to facilitate implant-to-ureter regeneration” [Chem. Eng. J. Volume 523 (2025) 168846] - Baiyang Song; Zonghuan Wang; Junjun Huang; Yiwei Hu; Fang Yang; Zewen Shi; Yuhao Cao; Li Fang; Hao Rong; Zejun Yan; Junhui Jiang; Ruoyu Zhang; et al. (Chemical Engineering Journal, 2025)

Regulation of cell migration through cross-sectional morphology design to facilitate implant-to-ureter regeneration - Baiyang Song; Zonghuan Wang; Junjun Huang; Yiwei Hu; Fang Yang; Zewen Shi; Yuhao Cao; Li Fang; Hao Rong; Zejun Yan; Junhui Jiang; Ruoyu Zhang; et al. (Chemical Engineering Journal, 2025)

Unraveling the impact of polystyrene microplastics with varying particle sizes and concentrations on lipid in vitro digestion and ex vivo absorption - Hongyu Zhu; Peng Wu; Zejun Hu; Haozhi Chen; Ni Wang; Xiao Dong Chen (Journal of Hazardous Materials, 2025)

Design, construction and application of an in vitro bionic small intestine absorption model based on dialysis membranes - Luping Wang; Zejun Hu; Peng Wu; Zhenkai Liao; Qiyang Ding; Ke Wang; Timothy V. Kirk; Xiao Dong Chen (Food and Bioproducts Processing, 2025)

Enhancing DHA algal oil delivery with emulsions: Impact of high-pressure homogenization and ultrasonication on in vitro digestion and ex vivo absorption efficiency - Yiqing Chen; Peng Wu; Zejun Hu; Luping Wang; Xia Jin; Xiao Dong Chen (Innovative Food Science & Emerging Technologies, 2025)

Fine-mapping of sm6.1, a novel locus conferring resistance to gray leaf spot from Solanum habrochaites accession LA1777 - Xiaoxiao Lu; Xin Li; Chunyang Pan; Junling Hu; Feng Pan; Lianfeng Shi; Chen Zhang; Ranran Zhang; Zejun Huang; Can Zhu; Yanmei Guo; Xiaoxuan Wang; et al. (Theoretical and Applied Genetics, 2025)

Regulating crystal faces and pore size of layered double oxides for efficient phosphorus recovery from water - Qin Zhang; Xueyv Shi; Lei Wang; Qipeng Li; Ruqin Xiong; Zejun Zhang; Bingde Wu; Congyang Yv; Xin Hu; Shengjian Li; Xiangjun Yang (Journal of Water Process Engineering, 2025)

Unlocking the release, digestion and absorption kinetics of DHA from different fish oil delivery systems: An in vitro and ex vivo study - Maoshuai Jiang; Zejun Hu; Xiao Dong Chen; Peng Wu (Food Hydrocolloids, 2025)

Mechanism and model of current response of hydroxylamine nitrate-based energetic polymer electrolytes under high voltage - Zejun Hu; Jianjun Wu; Zhicheng He; Yu Zhang; Yang Li; Qinhui Peng; Shiqichang Wu (Chemical Engineering Journal, 2025)

Brain metastases lung adenocarcinoma patients with BRG1 loss have a grim prognosis, featuring unique morphological and methylation characteristics - Junjie Yang; Jing Feng; Zejun Duan; Xing Liu; Hongwei Zhang; Mingshan Zhang; Zhong Ma; Zejuan Hu; Lei Xiang; Xueling Qi (Clinical & Experimental Metastasis, 2025)

Curcumin-loaded microcapsules with soy and whey protein as wall material: In vitro release, and ex vivo absorption based on the rat small intestine - Luping Wang; Peng Wu; Zejun Hu; Yiqing Chen; Xia Jin; Ruoxuan Deng; Timothy V. Kirk; Xiao Dong Chen (Journal of Food Engineering, 2024)

Effects of climate warming on soil nitrogen cycles and bamboo growth in core giant panda habitat - Dongyao Zhang; Hongbo Yang; Jindong Zhang; Min Xu; Weihua Xu; Jianchao Fu; Bin Feng; Hu Zhang; Qiongyu Huang; Daifu Wu; Zejun Zhang; Melissa Songer; et al. (Science of The Total Environment, 2024)

Impact of wall materials and DHA sources on the release, digestion and absorption of DHA microcapsules: Advancements, challenges and future directions - Maoshuai Jiang; Zejun Hu; Yixiao Huang; Xiao Dong Chen; Peng Wu (Food Research International, 2024)

Genetic analysis of inflorescence length in Solanum pimpinellifolium - Junling Hu; Xin Li; Hui Zhang; Xiaoxiao Lu; Feng Pan; Chunyang Pan; Wenyue Su; Min Zhang; Maomao Xu; Chen Zhang; Lianfeng Shi; Yanmei Guo; et al. (Genetic Resources and Crop Evolution, 2024)

Quadruple-branched jellyfish-like demulsifier used for completely demulsifying water-in-oil emulsion at low temperature and its demulsification mechanism - Liwei Shen; Tianqi Liu; Huan Li; Shuman Li; Zhijie Hu; Xuebin Jiang; Hanjun Liu; Zejun Zhang; Yuanzhu Mi; Weichu Yu (Fuel, 2024)

Synthesis and demulsification mechanism of an ionic liquid with four hydrophobic branches and four ionic centers - Qian Qu; Huan Li; Shuman Li; Zhijie Hu; Mingzhao Zhu; Junhong Chen; Xuebiao Sun; Yuqi Tang; Zejun Zhang; Yuanzhu Mi; Weichu Yu (Chemosphere, 2023)

Meta-analysis of microbial source tracking for the identification of fecal contamination in aquatic environments based on data-mining - Zejun Liu; Yingying Lin; Yanhong Ge; Ziyue Zhu; Jinlong Yuan; Qidong Yin; Bingjun Liu; Kai He; Maochuan Hu (Journal of Environmental Management, 2023)

Novel macromolecular synthetic phenolic antioxidants in sludge on a national scale in China: Their distribution, potential transformation products, and ecological risk - Yaqian Xu; Yu Hu; Tingting Ding; Zejun Wang; Chongshen Zhou; Qingqing Zhu; Thanh Wang; Ligang Hu; Shu-Shen Liu; Chunyang Liao; Jay Gan; Guibin Jiang (Science of The Total Environment, 2023)

Mass transfer during surfactant-enhanced DNAPL remediation: Pore-scale experiments and new correlation - Zejun Wang; Zhibing Yang; Ran Hu; Yi-Feng Chen (Journal of Hydrology, 2023)

Interface strengthening and high-value recycling of epoxy resin/carbon fiber fabric composites - Haifeng Xu; Jiarui Hu; Xin Liu; Huanghu Wu; Yu Jiang; Zejun Xu; Sufang Chen; Tingcheng Li; Junheng Zhang; Daohong Zhang (Chemical Engineering Journal, 2023)

Inbreeding and inbreeding avoidance in wild giant pandas - Yibo Hu; Yonggang Nie; Wei Wei; Tianxiao Ma; Russell Van Horn; Xiaoguang Zheng; Ronald R. Swaisgood; Zhixin Zhou; Wenliang Zhou; Li Yan; Zejun Zhang; Fuwen Wei (Molecular Ecology, 2017)
Inbreeding can have negative consequences on population and individual fitness, which could be counteracted by inbreeding avoidance mechanisms. However, the inbreeding risk and inbreeding avoidance mechanisms in endangered species are less studied. The giant panda, a solitary and threatened species, lives in many small populations and suffers from habitat fragmentation, which may aggravate the risk of inbreeding. Here, we performed long‐term observations of reproductive behaviour, sampling of mother–cub pairs and large‐scale genetic analyses on wild giant pandas. Moderate levels of inbreeding were found in 21.1% of mating pairs, 9.1% of parent pairs and 7.7% of panda cubs, but no high‐level inbreeding occurred. More significant levels of inbreeding may be avoided passively by female‐biased natal dispersal rather than by breeding dispersal or active relatedness‐based mate choice mechanisms. The level of inbreeding in giant pandas is greater than expected for a solitary mammal and thus warrants concern for potential inbreeding depression, particularly in small populations isolated by continuing habitat fragmentation, which will reduce female dispersal and increase the risk of inbreeding.

Withered on the stem: is bamboo a seasonally limiting resource for giant pandas? - Youxu Li; Ronald R. Swaisgood; Wei Wei; Yonggang Nie; Yibo Hu; Xuyu Yang; Xiaodong Gu; Zejun Zhang (Environmental Science and Pollution Research, 2017)

Progress in the ecology and conservation of giant pandas - Fuwen Wei; Ronald Swaisgood; Yibo Hu; Yonggang Nie; Li Yan; Zejun Zhang; Dunwu Qi; Lifeng Zhu (Conservation Biology, 2015)
Giant panda (Ailuropoda melanoleuca) conservation is a possible success story in the making. If extinction of this iconic endangered species can be avoided, the species will become a showcase program for the Chinese government and its collaborators. We reviewed the major advancements in ecological science for the giant panda, examining how these advancements have contributed to panda conservation. Pandas’ morphological and behavioral adaptations to a diet of bamboo, which bear strong influence on movement ecology, have been well studied, providing knowledge to guide management actions ranging from reserve design to climate change mitigation. Foraging ecology has also provided essential information used in the creation of landscape models of panda habitat. Because habitat loss and fragmentation are major drivers of the panda population decline, efforts have been made to help identify core habitat areas, establish where habitat corridors are needed, and prioritize areas for protection and restoration. Thus, habitat models have provided guidance for the Chinese governments’ creation of 67 protected areas. Behavioral research has revealed a complex and efficient communication system and documented the need for protection of habitat that serves as a communication platform for bringing the sexes together for mating. Further research shows that den sites in old‐growth forests may be a limiting resource, indicating potential value in providing alternative den sites for rearing offspring. Advancements in molecular ecology have been revolutionary and have been applied to population census, determining population structure and genetic diversity, evaluating connectivity following habitat fragmentation, and understanding dispersal patterns. These advancements form a foundation for increasing the application of adaptive management approaches to move panda conservation forward more rapidly. Although the Chinese government has made great progress in setting aside protected areas, future emphasis will be improved management of pandas and their habitat.

What determines selection and abandonment of a foraging patch by wild giant pandas (Ailuropoda melanoleuca) in winter? - Zejun Zhang; Xiangjiang Zhan; Li Yan; Ming Li; Jinchu Hu; Fuwen Wei (Environmental Science and Pollution Research, 2009)